Mortality and potential years of life lost in five zones of Medellin, 2004-2006 - Doris Cardona A; Ángela M. Segura C; Dedsy Y. Berbesí F (Universidad de Antioquia, 2011)
The mortality patterns observed in Medellín (Colombia) are different for each geographical zone of the city. This results in a loss of years of life and a consequent decrease in life expectancy. Such situation depends on the individuals' place of residence. Objective: to describe the mortality trends in five zones of Medellin, during the 2004-2006 period based on a mortality profile analysis by type of cause, age, gender, life expectancy, and potential years of life lost. Methodology: a descriptive study using the following sources of secondary data‎: mortality records (from 2004 to 2006) and the 2005 population census. The calculated measurements were: life expectancy, gross and specific rates, and potential years of life lost. Results: the death rate in Medellin was 4.8 per 1,000 people, with higher risk in extreme age groups. Men ages 20 to 29 are four times as likely to die as women. The highest risk was registered in the east central area (rate of 5.9) as well as in the west central area (rate of 5.4). The main cause of death is cardiovascular disease, and other causes. External causes were responsible for the highest amount of potential years of life lost. Conclusions: the inhabitants of the city's east center area showed a higher risk of death, mainly due to cardiovascular diseases and other causes. The lowest risk was observed in the Northwest zone, but external causes generated a decrease in potential years of life for the city's labor power and life expectancy.